200°C normally off AlGaN/GaN MISFET with 321 mA/mm drain current density and 1055 V breakdown voltage. Issue 5 (1st March 2019) - Xu, Zhe; Zhou, Yang; Li, Juntao
Abstract : A high‐performance normally off recess‐gated aluminium gallium nitride (AlGaN)/GaN metal–insulator–semiconductor field‐effect transistor (MISFET) is successfully demonstrated with operation temperature of 200°C which was fabricated by using a self‐terminating gate recess etching technique. At 200°C, by employing a high‐quality aluminium oxide/silicon nitride bilayer as gate dielectrics, the fabricated device exhibits a high threshold voltage of 4.5 V, a high drain current density of 321 mA/mm, a low off‐state leakage current of 20 μA/mm as well as a high on/off current ratio of ∼10 6 . Furthermore, a high forward gate breakdown voltage of 23.6 V (∼7.9 MV/cm) and an off‐state breakdown voltage as high as 1055 V are obtained in the fabricated device, both of which, as far as it is known, is the highest reported value in normally off GaN devices operated at 200°C. The high threshold voltage, large drain current density, low off‐state leakage current, high gate breakdown voltage as well as high off‐state breakdown voltage make this normally off recess‐gated AlGaN/GaN MISFET very suitable for high‐temperature power switch applications.